EFFECT OF GERMINATION AND COOKING ON IRON CONTENT, PHYTIC ACID AND LECTINS OF FOUR VARIETIES OF CHILEAN BEANS (Phaseolus vulgaris). - Christopher González Ponce; Ruth Marcela Ortega Rojas; Sumito Estevez; T Poblete; K Rebolledo; C Barrera; D Ulloa; M Valenzuela; C Valenzuela; E Pavez; R Mendoza; C Narbona; et al. (Journal of the Chilean Chemical Society, 2020)
The family of Fabaceae has been fundamental into the traditional nutrition in South America, including Chile, however in this country has reduce consumption of legumes between children in school age. This investigation pursued establish the impact over nutritional and no nutritional composition of chilean beans (Phaseolus vulgaris) exposed to cook and germination. The results obtained has shown the cooked samples has decreased the contain of iron and also diminished in total minerals from ashes analysis, instead the germinated samples increased both. Total proteins determined by Kjeldahl method exhibit no change for cooked and germinated beans in relation to control without treatment, while phytic acid increased and lectins decreased with the action of cook or germination of P.vulgaris. All the analysis was supported by statistical assessment and suggest the beans germination is a good alternative to improve the variety of recipes available to prepare beans in other attractive presentations on the subject of promote the children intake.